Fracture resistance of endodontically treated teeth with different heights of crown ferrule restored with prefabricated carbon fiber post and composite resin core by intermittent loading - de Oliveira, Jonas Alves; Pereira, Jefferson Ricardo; do Valle, Accacio Lins; Zogheib, Lucas Villaca [UNESP] (Mosby-elsevier, 2008)
This study evaluated the fracture resistance of endodontically treated teeth restored with prefabricated carbon fiber posts and varying quantities of coronal dentin. Sixty freshly extracted upper canines were randomly divided into groups of 10 teeth each. The specimens were exposed to 250,000 cycles in a controlled chewing simulator. All intact specimens were subjected to a static load (N) in a universal testing machine at 45 degrees to the long axis. Data were analyzed by 1-way analysis of variance and Tukey test (alpha = .05). Significant differences (P < .001) were found among the mean fracture forces of the test groups (positive control, 0 mm, 1 mm, 2 mm, 3 mm, and negative control groups: 1022.82 N, 1008.22 N, 1292.52 N, 1289.19 N, 1255.38 N, and 1582.11, respectively). These results suggested that the amount of coronal dentin did not significantly increase the fracture resistance of endodontically treated teeth restored with prefabricated carbon fiber post and composite resin core. (Oral Surg Oral Med Oral Pathol Oral Radiol Endod 2008;106:e52-e57)